2000
DOI: 10.1136/jramc-146-03-11
|View full text |Cite
|
Sign up to set email alerts
|

Day Case Rhinoplasty

Abstract: Rhinoplasty is considered by many to be an inpatient surgical procedure. This may be because the operation is thought to be traumatic with a risk of epistaxis and periorbital haematoma. Since 1992 rhinoplasty surgery at St George's hospital has been routinely performed on a planned day case basis. The hospital records of 97 patients were examined of which 17 patients (18%) underwent planned admission and 12 (12%) unplanned admission. No patients were re-admitted to hospital after discharge. With the advances i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…In this respect, the overall admission rate of 3.4 per cent, is considered borderline, according to the Royal College of Surgeons guidelines which have a set a target of two to three per cent readmission rate for day-case procedures, 1 and it is higher than a published rate of 0.7 per cent out of 10.000 general surgical, orthopaedic and gynaecological procedures. 8 However, it compares favourably with septoplasty performed as a day case (quoted admission rates of 5.4 per cent, 3 10.5 per cent 5 and ve per cent 4 ) while a retrospective day-case rhinoplasty study reports a rate of 12 per cent of unplanned admissions. It must be taken into account that the one patient who was admitted did not require any assessing day case septorhinoplasty: a prospective audit study using patient-based indices further intervention or packing and was discharged the following day.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this respect, the overall admission rate of 3.4 per cent, is considered borderline, according to the Royal College of Surgeons guidelines which have a set a target of two to three per cent readmission rate for day-case procedures, 1 and it is higher than a published rate of 0.7 per cent out of 10.000 general surgical, orthopaedic and gynaecological procedures. 8 However, it compares favourably with septoplasty performed as a day case (quoted admission rates of 5.4 per cent, 3 10.5 per cent 5 and ve per cent 4 ) while a retrospective day-case rhinoplasty study reports a rate of 12 per cent of unplanned admissions. It must be taken into account that the one patient who was admitted did not require any assessing day case septorhinoplasty: a prospective audit study using patient-based indices further intervention or packing and was discharged the following day.…”
Section: Discussionmentioning
confidence: 97%
“…Rhinoplasty is a procedure that is being performed routinely as a day case or even under local anaesthetic with sedation in the USA; however, in the UK it is generally considered an in-patient procedure. One series of patients having undergone day-case rhinoplasty 5 was recently published, but no prospective studies have been performed yet, and as such it can be considered as a new procedure in the UK. Whenever a new intervention is introduced, we feel that it is important to explore and record patients' experiences, as well as record objective results; this is the aim of outcome studies.…”
Section: Introductionmentioning
confidence: 99%
“…Other rhinology day case surgery published apart from septoplasty includes work done by Danielsen [10] who described out-patient endoscopic ethmoidectomy without complications. Banfield, et al [11] and Georgalas, et al [12] published on day case rhinoplasty and septorhinoplasty and reported an admission rate of 15% and 3% respectively. The re-admission rates associated with day-case septoplasty, mainly due to bleeding, ranged from 2% [9], 5% [13], 8.8% [14] to 11.4% [15].…”
Section: Discussionmentioning
confidence: 99%
“…Banfield et al 18 and Georgalas et al 19 described rhinoplasty admission rates of 15% and 3%, respectively, with Danielsen 20 having described day-case functional endoscopic sinus surgery without complication. Again, our experience confirms these procedures as practicable for a daycase approach.…”
Section: Discussionmentioning
confidence: 99%